The impact of body mass index on prognosis in patients with colon carcinoma - Fuchs, Julian; Schellerer, Vera S.; Brunner, Maximilian; Geppert, Carol-Immanuel; Grützmann, Robert; Weber, Klaus; Merkel, Susanne (International Journal of Colorectal Disease, 2022)
Background: The impact of body mass index (BMI) on prognosis in patients with curatively resected stage I–III colon carcinoma was analyzed. Methods: The prospectively collected data of 694 patients who underwent complete mesocolic excision between 2003 and 2014 were analyzed. BMI was classified into four categories: underweight (BMI < 18.5 kg/m2; n = 13), normal weight (BMI 18.5 to 24.9 kg/m2; n = 221), overweight (BMI 25.0 to 29.9 kg/m2; n = 309), and obese (BMI ≥ 30.0 kg/m2; n = 151). Univariate and multivariate analyses for comparison of prognosis were performed. Results: The 5-year rate of locoregional recurrence in all 694 patients was 2.1%, and no differences were found with respect to BMI (p = 0.759). For distant metastasis, the 5-year rate for all patients was 13.4%, and BMI did not have a significant impact (p = 0.593). The 5-year rate of disease-free survival for all 694 patients was 72.4%. The differences with respect to BMI were not found to be significant in univariate analysis (p = 0.222). In multivariate Cox regression analysis, disease-free survival was significantly better in obese patients (HR 0.7; p = 0.034). Regarding overall survival, the 5-year rate for all patients was 78.1%. In univariate analyses, no significant differences were found for BMI (p = 0.094). In the Cox regression analysis, overweight and obese patients had significantly better survival (overweight: HR 0.7; p = 0.027; obese: HR 0.6; p = 0.019). Conclusion: The better survival of overweight and obese patients in multivariate analyses must be interpreted with caution. It is influenced by several factors and seems to correspond to the phenomenon of the obesity paradox.
CRIS-Team Scopus Importer:2022-04-22
Keywords: Body mass index; Colon carcinoma; Obesity paradox; Overall survival; Prognosis